A digitalization-based approach for dismantling a cooling tower using a remotely controlled demolition excavator - Shakoorianfard, Masoud; Waurich, Volker; Richter, Christian; Will, Frank (Construction Robotics (Online), 2025)
The dismantling of cooling towers demands controlled demolition techniques in cases in which they are surrounded by other structures. As one of these methods, a remotely controlled demolition excavator is adopted to dismantle the cooling tower from the top in a successive manner. Since direct visual contact plays a pivotal role in this method, the operator’s workstation must be located on top of the cooling tower to guarantee a visible line of sight. This remote handling system, however, is subject to several limitations that hinder a continuous and quality demolition operation. Hence, this research presents a novel teleoperation system to tackle these issues. In this system, a digitalization-based approach is employed to set the stage for real-time visualization of the process, opening up the possibility of handling the demolition excavator from a distant location on the ground. To realize this system, various elements, including sensors, processing units, and communication infrastructure, are added to the machine to collect, process, and transmit required information, respectively. A light detection and ranging (LiDAR) sensor combined with point cloud processing techniques is utilized regarding the cooling tower wall sensing. This information paves the way for the real-time visualization of the demolition excavator and the wall section in a virtual environment created and rendered using the Unity game engine. Not only does this method outperform the conventional method in safety and efficiency, but it also provides lower latency and improved depth perception compared to a camera-based system, thereby being evaluated as a suitable method for future demolition operations and various applications in the construction industry.